2002
DOI: 10.1038/nbt763
|View full text |Cite
|
Sign up to set email alerts
|

Functional gene screening in embryonic stem cells implicates Wnt antagonism in neural differentiation

Abstract: The multilineage differentiation capacity of mouse embryonic stem (ES) cells offers a potential testing platform for gene products that mediate mammalian lineage determination and cellular specialization. Identification of such differentiation regulators is crucial to harnessing ES cells for pharmaceutical discovery and cell therapy. Here we describe the use of episomal expression technology for functional evaluation of cDNA clones during ES-cell differentiation in vitro. Several candidate cDNAs identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
251
5
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(275 citation statements)
references
References 48 publications
13
251
5
2
Order By: Relevance
“…On the other hand, exogenous Wnt-3a was shown to support the expansion and maintenance of hES cells [65]. In mES cells, the secreted Wnt antagonist sFRP2 stimulates production of neural progenitors [58]. In the same study, activation by canonical Wnt-1 and LiCl blocked differentiation, supporting a model in which inhibition of canonical Wnt signaling is required for neuronal differentiation.…”
Section: Human Neural Stem and Progenitor Cells: Wnt Ligands And Recementioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, exogenous Wnt-3a was shown to support the expansion and maintenance of hES cells [65]. In mES cells, the secreted Wnt antagonist sFRP2 stimulates production of neural progenitors [58]. In the same study, activation by canonical Wnt-1 and LiCl blocked differentiation, supporting a model in which inhibition of canonical Wnt signaling is required for neuronal differentiation.…”
Section: Human Neural Stem and Progenitor Cells: Wnt Ligands And Recementioning
confidence: 82%
“…Wnt-1 KO Altered central and peripheral neuronal development during initial axonogenesis [54] Wnt-1 KO Impaired midbrain development [55] Wnt-1 dominant negative Impaired hippocampal neurogenesis and spatial and object recognition memory [56,57] Wnt-1 overexpression Reduced neural differentiation of mESCs (also by treatment with lithium chloride) [58] Wnt-1 KO Increased differentiation into DA neurons in KO mESCs [59] Wnt-2 KO Decreased progenitor proliferation and neurogenesis in the ventral midbrain [60] Wnt-2 overexpression Induced dendritic arborization in hippocampal progenitors [61] Wnt-3 overexpression Increased differentiation of cortical intermediate [43] progenitors Wnt-3 overexpression Induced differentiation through cleavage of RYK in cortical progenitors [62] Wnt-3a KO Loss of the hippocampus [42] Recombinant Wnt-3a Induced GABAergic neuronal differentiation through RYK, reduced oligodendrogenesis [63] Recombinant Wnt-3a Induced differentiation of hESCs [64] Recombinant/purified Wnt-3a…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
“…First, a 5Ј-EcoRV/XhoI-3Ј PCR fragment containing the entire coding sequence of mouse Nanog (see supplemental data, Note 2) was amplified from CGR8 RNA and cloned between the EcoRV and XhoI sites in pBSK-STAT3-ER T2 (36) to generate pBSK-Nanog-ER T2 . 3 Second, a blunt BamHI fragment containing Nanog-ER T2 from pBSK-Nanog-ER T2 was subcloned into the blunted EcoRI site in the pPyCAGIZ bicistronic supertransfection vector (5) (which contains an Ori sequence allowing extrachromosomal replication upon transfection into cells expressing polyoma large T antigen) (37), generating pPyCAGIZ-Nanog-ER T2 .…”
Section: Experimental Proceeduresmentioning
confidence: 99%
“…500 ng/ml Tet was added back to control samples. To generate Nanog-ER T2 cells, ES cells expressing the polyoma large T antigen (E14/T cells) (37) were electroporated (200 V, 960 F) with 20 g of pPCAGIZ-Nanog-ER T2 . Cells were plated at 5 ϫ 10 5 cells/10-cm dish and cultured in the presence of LIF (1000 units/ml) plus zeocin (1 g/ml) for 8 days and resistant colonies pooled and expanded.…”
Section: Experimental Proceeduresmentioning
confidence: 99%
“…It has also been shown that dual ESCs [98]. Likewise, the Wnt antagonist, Sfrp2, stimulates the production of neural progenitors, whereas the overexpression of Wnt-1 inhibits neural differentiation of mouse ESCs [99]. FGF4…”
Section: L-type Ca 2+ Channelsmentioning
confidence: 99%